2005
DOI: 10.1016/j.jvs.2005.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Open surgical repair of children less than 13 years old with lower extremity vascular injury

Abstract: Vascular blunt injury is especially insidious in children. However, an aggressive approach of vascular repair, even extensive bypasses with reverse vein, will allow limb salvage in the absence of a diagnostic delay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 23 publications
0
31
0
2
Order By: Relevance
“…Amputations are typically only needed for patients with mangled extremities (eg, lawn mower injury) and/or delayed presentation. 4 Dalsing et al reported on late follow-up of three patients with reversed saphenous vein grafts (21-49 months), none of whom experienced graft stenosis or dilatation on duplex ultrasound scan. Dorweiler et al reported excellent patency among adults receiving vein interposition grafts after arterial trauma; on follow-up of 23 to 139 months, there were no late thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Amputations are typically only needed for patients with mangled extremities (eg, lawn mower injury) and/or delayed presentation. 4 Dalsing et al reported on late follow-up of three patients with reversed saphenous vein grafts (21-49 months), none of whom experienced graft stenosis or dilatation on duplex ultrasound scan. Dorweiler et al reported excellent patency among adults receiving vein interposition grafts after arterial trauma; on follow-up of 23 to 139 months, there were no late thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Довжина діастазу, що перевищує 3-5 см, неминуче потребує судинного протезування, для цього застосо-вують перевернуті вени рук, велику чи малу підшкірну вену, поверхневу стегнову вену з непошкоджених діля-нок [11,16,29]. Велика підшкірна вена в дітей менша й тендітніша, ніж у дорослих, а її виділення супрово- Огляди та дискусії / Reviews and Discussions джується вираженими травмами медії та інтими, тому фахівці рекомендують виділяти судину максимально акуратно, без розтягів, зберігати в теплій гепаринізо-ваній крові [11].…”
Section: результати й обговоренняunclassified
“…Судинні шви накладають перервними монофіламент-ними нитками 6-0 або 7-0 [8,16,19]. Застосування безперервних швів у дитячому віці може призвести до звуження анастомозу, хоча клінічних порівнянь без-перервних і вузлових швів у дітей не проводилось [23].…”
Section: результати й обговоренняunclassified
“…In children, duplex ultrasound can confirm occlusion and can localize the site of injury as well as diagnose an AV fistula or pseudoaneurysm. 7 This modality can also help differentiate between vasospasm and arterial thrombosis. CTA is now being used more often for diagnosis of vascular injuries in children and has been shown to be more reliable for truncal and great vessel injuries than distal ones ( Fig.…”
Section: Demographics and Etiologymentioning
confidence: 99%